2022
DOI: 10.1002/puh2.9
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the issue of access to medicines in Africa: Challenges and recommendations

Abstract: Background: Access to safe, effective, affordable, and quality medicines is an essential component of the right to health and is also one of the targets in the global development agenda. In this review article, we extensively discuss the challenges and issues surrounding access to medicines in the African region as well as provides recommendations for ensuring medicines security on the continent. Methods: We conducted narrative review with the use of data reported in published literature, reports, and grey lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 62 publications
0
48
0
Order By: Relevance
“…Inspection efforts by the Ministry of Public Health would need to be bolstered to discourage smuggling by distributors and pharmacists. Evidence shows that the lack of a functioning and sustainable drug supply chain is a major reason for poor access to essential drugs [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inspection efforts by the Ministry of Public Health would need to be bolstered to discourage smuggling by distributors and pharmacists. Evidence shows that the lack of a functioning and sustainable drug supply chain is a major reason for poor access to essential drugs [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Access to medicines and healthcare also remains challenging in Africa due to dependency on Western donor funding grounded on weak sustainable health financing, thus limiting the optimization of quality health among the vast majority [7]. This dependency was exposed during the advent of COVID‐19 and the Ebola outbreak, revealing the vulnerability and risk of the continent's reliance [8].…”
Section: Issues Affecting Medicines Manufacturing and Access In Africamentioning
confidence: 99%
“…TAM such as herbal medicines play a significant role in the public health architecture of emerging economies. Close to 80% of Africa's 1.4 billion inhabitants make use of TAM [ 3 ]. While the figure for fake TAM may not be known (albeit a growing phenomenon), the WHO has reported that Africa alone accounts for 42% of all global cases of counterfeit and substandard medicines [ 4 ].…”
Section: Introductionmentioning
confidence: 99%